The Role of Cooperatives in Strengthening Entrepreneurial Characteristics and Opportunity Identification Competencies of Rural Women in Kermanshah Province - elham emami; gholamhossein hosseininia; Ahmad Yaghoubi Farani (تعاون و کشاورزی, 2018)
The main purpose of this research was to examine the role of cooperatives functions in strengthening entrepreneurial characteristics and opportunity identification competencies of rural women in Kermanshah province. This study was conducted in a survey method using the views of 131 rural women members of rural cooperatives. The data gathering tool was a questionnaire that its validity was confirmed by a panel of experts in the field of entrepreneurship and co-operative and Cranach’s alpha method was used to calculate the reliability of the instrument that the values obtained showed the relevance of questions and items for different sectors of the questionnaire. Based on correlation coefficients, a positive and significant correlation was found between all aspects of cooperative functions with strengthening entrepreneurial characteristics and opportunity identification competencies of rural women as two dependent variables. Regression analysis also showed that the three functions of cooperatives like market supply and development, strengthening personal motivations and capabilities, and providing capital and production infrastructure can explain 58.2% of changes of strengthening entrepreneurial characteristics as dependent variable.  Also 42.7% of changes in rural women’s opportunity identification competencies explained by three functions like market supply and development, providing capital and production infrastructure, and education and information related functions.